Health-related quality of life in type 1 and type 2 diabetic patients in a Portuguese central public hospital - Sepúlveda E; Poínhos R; Constante M; Pais-Ribeiro J; Freitas P; Carvalho D (Diabetes, Metabolic Syndrome and Obesity, 2015)
Eduardo Sepúlveda,1,2 Rui Poínhos,2,3 Miguel Constante,4,5 José Pais-Ribeiro,1,2 Paula Freitas,6,7 Davide Carvalho6,71Faculty of Psychology and Educational Sciences, University of Porto, Porto, Portugal; 2Associação de Prevenção e Apoio à Diabetes, Porto, Portugal; 3Faculty of Nutrition and Food Sciences, University of Porto, Porto, Portugal; 4Institute of Psychiatry, King’s College London, London, UK; 5Department of Psychiatry, Hospital Beatriz Ângelo, Loures, Portugal; 6Department of Endocrinology, Diabetes and Metabolism, Centro Hospitalar São João, Porto, Portugal; 7Faculty of Medicine, University of Porto, Porto, PortugalBackground: Diabetes mellitus is a chronic metabolic disease, the prevalence of which has registered a considerable increase, mainly in adults and elderly. The purpose of this study was to assess the relationship between health-related quality of life in patients with diabetes and sex, body mass index, type of diabetes and treatment regimens (type 1 diabetes: intensive versus conventional treatment; type 2 diabetes: insulin use versus non-insulin use), and duration of diabetes.Methods: One hundred and twenty-four patients with diabetes were interviewed. Health-related quality of life was evaluated using the age-adjusted Short-Form 36 dimensions (physical functioning, role-physical, bodily pain, general health, vitality, social functioning, role-emotional, and mental health), and related to demographic and clinical variables. Independent samples t-tests and One-Way Analysis of Variance were used to compare means of independent samples. The degree of association between pairs of variables was measured by Pearson’s (r) or Spearman’s (rs) correlation coefficients.Results: The mean age of the study population was 55.7±16.4 years; 54.8% were male, and 77.4% had type 2 diabetes. Females reported worse quality of life than males in all dimensions of the Short-Form 36, except for role-physical and bodily pain. Obese patients had worse physical functioning than normal weight and overweight patients, and worse vitality than their normal weight counterparts. Type 2 diabetic patients taking insulin had lower physical functioning and vitality than those without insulin therapy. Longer duration of diabetes was associated with lower physical functioning, role-physical, general health, vitality, role-emotional, and mental health.Conclusion: Being female, obese, having type 2 diabetes and taking insulin, and having a longer disease duration are characteristics associated with worse age-adjusted quality of life in patients with diabetes.Keywords: clinical variables, demographic variables, diabetes mellitus, health-related quality of life